At the limits of "acceptable" speech: a feminist analysis of official discourse on child sexual abuse - Tucker, Katie (Feminist responses to injustices of the state and its institutions, 2024)
Official discourse on child sexual abuse (CSA) has the power to frame the issue and to shape responses to it. It is therefore crucial to critically engage with this discourse as it has, and continues to, contribute to dominant understandings of CSA that do not take into account its gendered nature. This chapter engages with the discursive framing of CSA between the years of 2010 and 2015 through some official responses to two high-profile cases - those of widescale CSA in the English towns of Rochdale and Rotherham. The chapter does this in order to provide a critical analysis of how CSA was ‘officially’ dealt with in this period, and whether this response opened up, or shut down, space for critical feminist understandings of the issue.